Experimental installation for evaluation of snowboard simulated onsnow dynamic performance - Subic, A.; Clifton, P.; Kovacs, J.; Mylonas, F.; Rochefort, A. (Procedia Engineering, 2010)
The paper presents an original dynamic experimental installation that has been designed and developed at RMIT University for the evaluation of snowboard simulated on-snow performance. The dynamic rig comprises two independent pneumatic cylinders to replicate rider foot movement, as well as three independent adjustable pressure airbags used to simulate the snowboarding terrain by varying their pressure according to the change in the terrain configuration. A custom designed, PLC control system allows for the simulation of common snowboard manoeuvres, from turns of varying board inclination, to nose or tail presses, board slides, and finally the performance of jumps. The PLC programs can be modified or re-written to simulate a variety of terrain features of interest to the investigation. Stress-strain characteristics of the snowboard tested under load are determined using a comprehensive strain gauge system. The paper presents in detail the design of the dynamic experimental installation, rig calibration and testing protocols.